DEPICTION OF SYMBOLS IN THE LORD VISHNU’S LOTUS FEET - Kumari, Aakansha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Lord Vishnu consider the one of important divine being among the Trimurti who is responsible to regulate, nourish and nurture the universe continuously by the sounds of Yagya. The Lord Vishu appears in many glorified forms in various ancient texts that shows Lord Vishnu is equivalent to various elements which nurture the universe. Apart from discussion the glory of foot prints of Lord Vishnu also mention in form of Symbols theses foot prints also worship by the Goddess Laxmi with devotion, faith and dedication. According to these believes following are the symbols of right and left foot of lord Vishnu. S.No.-Lotus Feet of Lord Vishnu- Depiction of Symbols 1-Right Foot-Joh (Barley), Chakra, Kamal, Urdhav Rekha (Vertical Line), Ankush (Goad), Dhwaj, Chatra, Vajra, Swastika, Anta-Kona, Jambu- Phala. 2-Left Foot-Shankha, Aakash, Dhanusha, Gaopad(Cow’sFoot), Kalasha, Tri-kona (Triangle), Ardha-Chandra, Matsya(Fish). Through this research paper, it is tried to describe the above mention symbols which reveals in various forms in our world.